Teresa Lanceta’s Modal Aesthetics - Tejero Fernández, Susana (Escritura e Imagen, 2019)
This article explains modal aesthetics concept. The theoretical frame is expound by different authors who defend aesthetics behaviour in human beings and their skills making art. Human experience is beauty if they establish a relation with the materia from the ontological and honest position and in regards to make an organic interaction to transform each other. Human and materia would reach an homogeneous status because of the effective knowledge (from ontological research) and experience will let they understand the nature of subject and object. This theory is contrasted with Teresa Lanceta’s work. Lanceta shows us a deep respect to the object and culture. Her work claims the emotion and the particular artist expression from an homogeneous relation with the object.